Assessing the Consequences of Natural Disasters on Sustainability in Rural Municipalities: Evidence from Loška Dolina - Bobek, Vito; Lipovac, Blanka; Horvat, Tatjana (Naše gospodarstvo/Our economy, 2025)
This study examines the impact of natural disasters on the sustainable development of the rural municipality of Loška Dolina, focusing on the 2014 ice storm and subsequent floods. Through semi-structured interviews with seven key stakeholders, including local government, civil protection, and affected individuals, the research analyzes the disasters' effects on the economic, social, and environmental pillars of sustainability. The ice storm damaged forests and infrastructure, while floods caused soil contamination and habitat disruption. Despite these challenges, the community showed resilience and increased climate awareness. The SWOT analysis highlights both opportunities in the timber industry and challenges in disaster preparedness. The study emphasizes integrating disaster risk reduction into sustainable development planning.